Ethiopian Agroclimate Advisory Platform (Edacap-V2): Forecast module co-learning with national partners - Ahmed, Jemal; Degefie, Tibebe; Desta, Lulseged; Teshome, Asaminew; Grossi, Amanda; Dessalegn, Olika; Ghosh, Aniruddha (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report presents the outcomes and reflections from the national Training of Trainers (ToT) workshop on the Forecast Module of the Ethiopian Digital Agro-Climate Advisory Platform (EDACaP-v2), held from June 16–18, 2025, at the ILRI campus in Addis Ababa. EDACaP is a nationally owned, end-to-end digital system designed to transform complex weather and climate data into timely, localized, and actionable advisories for Ethiopian farmers and agricultural planners. The training brought together technical experts from the Ethiopian Institute of Agricultural Research (EIAR), the Ethiopian Meteorological Institute (EMI), and the Ministry of Agriculture (MoA), with support from the Alliance of Bioversity International and CIAT and the AICCRA project. Over three days, participants engaged in a mix of expert presentations, hands-on technical sessions, and institutional dialogue focused on the operationalization of sub-seasonal-to-seasonal (S2S) forecasts for agricultural decision-making. The training introduced the principles of NextGen climate forecasting, tools for accessing and downscaling multi-model ensembles, integration with DSSAT crop simulation models, and techniques for generating and communicating advisory products. It also facilitated discussions on institutional roles, data readiness, and sustainability strategies. This report documents the technical content, highlights of the discussion, lessons learned, and strategic recommendations aimed at ensuring national ownership, deployment, and long-term scalability of EDACaP’s forecast-based advisory services.